Who’s still breeding flowers? - Schiva, T.; Mercuri, A. (Ornamental Horticulture, 2007)
The flower sellers’ customers, the only qualified to judge the value of the plant, are chiefly in search of beauty, and flowers, as subject of inspiration, cannot be less than perfect. The beauty in flowers means perfection and for applied researchers, faultless quality, result in a more pragmatic goal.